“Dare to Share”: Improving Information Sharing and Risk Assessment in Multiteam Systems Managing Offender Probation - Waring, Sara; Taylor, Ellise; Giles, Susan; Almond, Louise; Gidman, Vincent (Frontiers in Psychology, 2022)
Managing offenders released from prison requires a multiteam system (MTS) approach, with teams from across police, probation, and other criminal justice agencies. However, public inquiries highlight current approaches are impaired by poor information sharing that compromises risk assessment and recall decisions, which can allow serious further offences to occur. Little research has focused on the causes of these information sharing difficulties. The current study draws on the perspectives and experiences of probation and police officers to improve understanding of causes of information sharing difficulties. The research is conducted within the context of a new enhanced information sharing ‘Direct Access’ initiative implemented in one region of the UK (Devon and Cornwall) that permits probation to directly access police information technology systems. This provides a novel opportunity to cross validate MTS theory to the real-world context of offender management and considers what works in practise to overcome information sharing challenges. Eleven semi-structured interviews were conducted with police (N = 4) and probation (N = 7) officers. Thematic analysis revealed six themes: i) information sharing difficulties and impact; ii) causes of information sharing difficulties; iii) impact of ‘Direct Access’ on information sharing practices; iv) workload inequality; v) training; and vi) evolution of ‘Direct Access’. Overall, findings highlight that information sharing difficulties are causes by not knowing what information to request or share, limited resources, lack of clarity about General Data Protection Regulation and concern about consequences of breaching this. These barriers can result in delays and failures to share information, which hinders the accuracy of risk assessments and ability to safeguard. Findings also highlight that providing statutory partners with ‘Direct Access’ to I.T systems can improve the relevance and timeliness of information. However, ‘daring to share’ is not enough to address trust issues without also clarifying expectations regarding information use and perceived workload inequalities.